Ensaísmo de Paulo Leminski: panorama de um pensamento movente - Paula Renata Melo Moreira (2011)
The present thesis aims to delineate an intellectual profile of Paulo Leminski, conjugating for that purpose, his essays. Over two hundred essays were analyzed and partially presented in four chapters, which were divided according to the sort of publication: great press, alternative publications and those ones released on book. The intent is to realize how the theoretic-critical manifestations of this writer get into line with his poetical activity and in which way it configures an author whose intellectual posture is changeable, split, wandering.